2016
DOI: 10.1097/ccm.0000000000001877
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Time-Fixed Mortality Prediction Models and Their Effect on ICU Performance Metrics Using the Simplified Acute Physiology Score 3

Abstract: The recalibrated Simplified Acute Physiology Score 3 hospital outcome prediction model performed well on long-term outcomes. Evaluation of ICU performance using standardized mortality ratio was only modestly sensitive to the follow-up time. Our results suggest that 30-day mortality may be a good benchmark of ICU performance. However, the duration of follow-up must balance between what is most relevant for patients, most affected by ICU care, least affected by administrative policies and practically feasible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Second, the calibration and adjustment in the APACHE database over the duration of the study and variation in the patients' diagnoses in the ICU may affect the outcome prediction of the model. 34,35 The case mix adjuster in the APACHE system remained stable, suggesting that the patient variation did not significantly change over the 9-year time frame of data collection. The APACHE methods for adjusting for nonnormally distributed data are beyond the scope of this analysis and we are reporting mean values of the O/E LOS days pursuant to their standard reporting methods.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the calibration and adjustment in the APACHE database over the duration of the study and variation in the patients' diagnoses in the ICU may affect the outcome prediction of the model. 34,35 The case mix adjuster in the APACHE system remained stable, suggesting that the patient variation did not significantly change over the 9-year time frame of data collection. The APACHE methods for adjusting for nonnormally distributed data are beyond the scope of this analysis and we are reporting mean values of the O/E LOS days pursuant to their standard reporting methods.…”
Section: Discussionmentioning
confidence: 99%
“…We a priori decided on 90-day survival status as the outcome because we believe it is more meaningful than in-hospital mortality and not too long to be dominated by underlying nonacute disease states. 10 In addition, survival status was available at 90 days.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies from the Swedish Intensive Care Registry (SIR) have demonstrated the feasibility to capture long-term outcomes with minimal loss to follow-up. 12,13 Hence, we set out to investigate whether mortality up to one year among critically ill patients with severe sepsis has changed from 2008 to 2016 and also to study the nonsepsis ICU population for comparison. Additionally, we wanted to investigate if patient demographics and comorbidity have changed over the same period, and whether these factors were associated with mortality.…”
mentioning
confidence: 99%